2019
DOI: 10.3390/molecules24101861
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Desorption Properties of LiBH4/xLiAlH4 (x = 0.5, 1, 2) Composites

Abstract: A detailed analysis of the dehydrogenation mechanism of LiBH4/xLiAlH4 (x = 0.5, 1, 2) composites was performed by thermogravimetry (TG), differential scanning calorimetry (DSC), mass spectral analysis (MS), powder X-ray diffraction (XRD) and scanning electronic microscopy (SEM), along with kinetic investigations using a Sievert-type apparatus. The results show that the dehydrogenation pathway of LiBH4/xLiAlH4 had a four-step character. The experimental dehydrogenation amount did not reach the theoretical expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…The reversibility of pristine LiBH 4 demands harsh conditions (>600 • C and >100 bar H 2 ) [1,41], which makes it impossible for its direct use as a hydrogen storage medium for practical applications. Several investigations have been done heading towards thermodynamic destabilization and kinetic improvement of LiBH 4 [29,30,39,46,49,50,53,[58][59][60][61][62][63][64][65][66][67]69,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][89][90][91][92][93][94][95][96][97][98][99].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reversibility of pristine LiBH 4 demands harsh conditions (>600 • C and >100 bar H 2 ) [1,41], which makes it impossible for its direct use as a hydrogen storage medium for practical applications. Several investigations have been done heading towards thermodynamic destabilization and kinetic improvement of LiBH 4 [29,30,39,46,49,50,53,[58][59][60][61][62][63][64][65][66][67]69,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][89][90][91][92][93][94][95][96][97][98][99].…”
Section: Discussionmentioning
confidence: 99%
“…Table 4): the capacity was proved to be reduced by half in four cycles [74], or even degraded to~15% of the theoretically available H 2 content in 10 cycles [77]. The capacity loss may be due to the combination of several factors [74,[77][78][79][80][81] of reaction products on its surface. Recently, it was shown that the extent of the dehydrogenation reaction greatly depends on the precipitation and growth of reaction products (LiH, AlB 2 , and LiAl) on the Al surface.…”
Section: Additive Theoretical and Predicted Values Experimental Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with high cost cryogenic liquid storage and dangerous high compression gas tanks, hydrogen stored in solid-state materials shows easy manipulability temperature, low working pressure (Khafidz et al, 2016 ; Rusman and Dahari, 2016 ; Razavi et al, 2019 ). In the past decades, oceans of materials for hydrogen storage have been investigated, including physical adsorbents (carbon and MOF), complex hydrides (LiBH 4 , LiNH 4 , NaAlH 4 ), alloys hydrides (Mg 2 NiH 4 , TiFeH 2 , NaMgH 3 ), and metal hydrides (MgH 2 ) (Shao et al, 2015 ; Zhai et al, 2016 ; Xiao et al, 2017 ; Chen et al, 2019 ; Goto et al, 2019 ; He et al, 2019 , 2020 ; Liu H. et al, 2019 , 2020 ; Song et al, 2019 ; Jansa et al, 2020 ; Yao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The decomposition enthalpy values of LiBH 4 also reduced to 60.4 kJ/mol. He et al (2019) studied the dehydrogenation performance of LiBH 4 /LiAlH 4 composite, found that 8.7 wt.% of hydrogen was released at 500 • C, and defined a "Li-Al-B-H" compound. Soru et al (2014) focused on the phase structural transformation of the LiAlH 4 + LiBH 4 system, which can produce 6.8 wt.% of hydrogen.…”
Section: Introductionmentioning
confidence: 99%